The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.26815/acn.2020.00143
|View full text |Cite
|
Sign up to set email alerts
|

Serum Uric Acid as a Predictive Factor for Rotaviral or Noroviral Benign Convulsions with Mild Gastroenteritis

Abstract: Convulsions are a common problem in children. Benign convulsion with mild gastroenteritis (CwG) was first reported in Japan in 1982 [1], and is defined as an afebrile convulsion accompanied by symptoms of gastroenteritis in a child without a previous history of neurological disease or electrolyte abnormalities, moderate to severe dehydration, or metabolic acidosis. Longterm prognosis is favorable without serious sequelae. Most cases of CwG have been described in patients with rotavirus infection Purpose: This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 28 publications
(30 reference statements)
1
10
0
Order By: Relevance
“…A recent study found that an elevated level of serum uric acid is a factor for CwG [36]. In this study, we demonstrated that factors such as age and geographic location influenced RVGE and RaCwG differently; therefore, the prevalence of RaCwG is likely affected by various factors.…”
Section: Discussionsupporting
confidence: 51%
“…A recent study found that an elevated level of serum uric acid is a factor for CwG [36]. In this study, we demonstrated that factors such as age and geographic location influenced RVGE and RaCwG differently; therefore, the prevalence of RaCwG is likely affected by various factors.…”
Section: Discussionsupporting
confidence: 51%
“…Therefore, factors associated with the residence of the patients may affect the ratio of RaCwG to RVGE and NaCwG to NVGE. Furthermore, uric acid can be used as a diagnostic index for RaCwG; therefore, the effects of uric acid on the ratio of RaCwG to RVGE should be considered [ 47 ]. The ratio of NaCwG to NVGE consistently increased regardless of rotavirus vaccination.…”
Section: Discussionmentioning
confidence: 99%
“…11,17,30) Se-veral studies demonstrated that CwG may be associated with hyperuricemia or hyponatremia. 29,34,37) A recent study found that severe ketosis occurring in patients with CwG is associated with lower blood glucose and sodium levels. 35) Serum aspartate aminotransferase levels were elevated in patients with RaCwG compared with patients with RVGE without seizures or patients with febrile seizure associated with RVGE.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Although one of the characteristics of CwG is no abnormal findings in laboratory tests, some authors have conducted research with broader characteristic criteria of CwG [ 11 , 17 , 30 ]. Several studies demonstrated that CwG may be associated with hyperuricemia or hyponatremia [ 29 , 34 , 37 ]. A recent study found that severe ketosis occurring in patients with CwG is associated with lower blood glucose and sodium levels [ 35 ].…”
Section: Clinical Manifestationsmentioning
confidence: 99%